Stress hyperglycemia and poor outcomes in patients with ST-elevation myocardial infarction: a systematic review and meta-analysis - Alkatiri, Abdul Hakim; Qalby, Nurul; Mappangara, Idar; Zainal, Ahmad Taufik F.; Cramer, Maarten J.; Doevendans, Pieter A.; Qanitha, Andriany (Frontiers in Cardiovascular Medicine, 2024)
Hyperglycemia, characterized by elevated blood glucose levels, is frequently observed in patients with acute coronary syndrome, including ST-elevation myocardial infarction (STEMI). There are conflicting sources regarding the relationship between hyperglycemia and outcomes in STEMI patients. We aimed to compile evidence to assess the association between hyperglycemia and adverse outcomes.We conducted a comprehensive search for articles on PubMed and Embase using search strategies which yielded 4061 articles. After full-text screening, 66 articles were included for systematic review, and 62 articles were further selected for meta-analysis.The 66 included articles spanned the years 2005 to 2023. Of these, 45 articles reported admission blood glucose, 13 articles used HbA1c, and 7 articles studied fasting blood glucose. Most studies defined STEMI with primary PCI as their inclusion criteria. Mortality was the most often outcome reported related to hyperglycemia. Overall, 55 (83.3%) studies were at low risk of bias. Both admission and fasting blood glucose were significantly related to short-and long-term mortality after STEMI, with a pooled risk ratio (RR) of 3.02 (95%CI 2.65-3.45) and 4.47 (95% CI 2.54-7.87), respectively. HbA1c showed substantial association with long-term mortality (HR 1.69, 95% CI 1.31-2.18)) with a pooled RR of 1.58 (95% CI 1.26-1.97). In subsequent analyses, admission hyperglycemia was associated with an increased risk of reinfarction (pooled RR 1.69, 95% CI 1.31-2.17), heart failure (pooled RR 1.56, 95% CI 1.37-1.77), cardiogenic shock (pooled RR 3.68, 95% CI 2.65-5.11), repeat PCI or stent thrombosis (pooled RR 1.99, 95% CI 1.21-3.28), and composite major adverse cardiac and cerebrovascular events (MACCE) (pooled RR 1.99, 95% CI 1.54-2.58).Our study demonstrated that hyperglycemia has a strong association with poor outcomes after STEMI. Admission and fasting blood glucose are predictors for short-term outcomes, while HbA1c is more appropriate for predicting longer-term outcomes in STEMI patients.